Poop happened! : a history of the world from the bottom up - Albee, Sarah (Walker, 2010)
"Throughout the ages, the most successful civilizations were the ones who realized that everyone poops and they'd better figure out how to get rid of it! From the very first flushing toilet (invented way earlier than you would think) to the efficient Roman aqueducts (possibly inspired by the goddess of sewers!) to castles in the Middle Ages whose moats used more than just water to repel enemies, Poop happened! traces human civilization through this revolting yet fascinating theme."--Book jacket.